Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita - Abd Wahid; Mujib Hannan; Silvia Ratna Sari Dewi; Rabbaniyah Hariyati Hidayah (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
Stunting is a growth and development disorders in children under five (z-score TB / U <-2 SD). If this was allowed, it will have an impact on the welfare of a country in the future. The purpose of knowing the relationship between the relationship, offering breast milk, mother's education, father's education, income and number of family members with family incidents in children under five in Talang Village, Saronggi District. This type of observational analytic research with a case control design. The population was 133 children under five who were registered at the posyandu and their mothers. The sample consisted of 34 people who used simple random sampling technique which consisted of 17 cases and 17 control groups. Data collection using a questionnaire. Data analysis used the chi-square test and Fisher's Exact test. The results showed that children under five with stunting were 76.5% not exclusively breastfed, 76.5% had mothers with low education, 70.6% had fathers with low education, 70.6% were small family members, 82.4% were blessed income. Chi-square test analysis showed a relationship between the incidence of stunting in children under five with offering exclusive breastfeeding (p-value 0.037). The definitive analysis showed no correlation between the incidence of stunting and maternal education, education, family income and number of family members (-values ​​1,000, 1,000, 0.688, 1,000). Addressing the lack of good coordination and collaboration between the government and the community in reducing risk factors.